2020
DOI: 10.1002/aelm.202000976
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Level Switching and Reversible Current Driven Domain‐Wall Motion in Single CoFeB/MgO/CoFeB‐Based Perpendicular Magnetic Tunnel Junctions

Abstract: One of the critical issues in spintronics‐based technologies is to increase the data storage density. Current strategy is based on shrinking the devices size down to tens of nanometers, or several nanometers, which is reaching its limit. A new proposal is to use multi‐level cells (MLCs) to store more than two bits in each cell. In this work, the multi‐level switching is realized in CoFeB/MgO/CoFeB based nano‐scale single perpendicular magnetic tunnel junctions (p‐MTJs) with three or four stable resistance stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…We obtain p-TMR = 91%, J c = 2-3 × 10 10 A m −2 and resistance area product (RA) = 7.5 Ωµm 2 , which fit the requirements of the applications of p-STT-MRAMs [2]. A systemetic study of junction size dependent CIS has been reported in our previous study [18]. A small shift of CIS curve center is observed, most likely due to Néel-type and dipole coupling between the RL and FL, which can be affected by the size dependent homogeneous magnetization [19].…”
Section: Current-induced Switching and Thermovoltagesupporting
confidence: 77%
See 1 more Smart Citation
“…We obtain p-TMR = 91%, J c = 2-3 × 10 10 A m −2 and resistance area product (RA) = 7.5 Ωµm 2 , which fit the requirements of the applications of p-STT-MRAMs [2]. A systemetic study of junction size dependent CIS has been reported in our previous study [18]. A small shift of CIS curve center is observed, most likely due to Néel-type and dipole coupling between the RL and FL, which can be affected by the size dependent homogeneous magnetization [19].…”
Section: Current-induced Switching and Thermovoltagesupporting
confidence: 77%
“…After the nano-fabrication, the p-MTJs were annealed in vacuum conditions (∼1 × 10 −6 Torr) at 300 • C remaining 80 min without magnetic field. The CIS properties of the p-MTJs were characterized in four-probe method, where the DC current (I) was applied in two contacts, while the voltage (V) was measured in two crossed contacts [18].…”
Section: Methodsmentioning
confidence: 99%
“…[ 25 , 77 ] Recently, many efforts have been made to develop multiple‐valued memories considering various strategies. [ 78 , 79 , 80 , 81 , 82 , 83 , 84 ] However, a successful design has not been achieved. In this context, our MVL device concept based on NCO films appears particularly promising.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the reported multistate realizations are based on in-plane magnetic anisotropic structures or geometric device fabrications with domain wall motion (DWM) models, e.g., the experimental demonstration of the two-level device based on DWM in a spin valve, [38] three-level device with the half-ring shape, [39] and four-state MTJ switchable with SOT. [40] Despite the available reports on pure simulation and prototype DW-MTJ devices, [8,[41][42][43][44][45] development is hindered by system integration and operation efficiency limits. Explicitly, to date, few functional implementations exist of SOT-MTJ devices with reliable and switchable multistates in a synthetic, CMOS compatible, and field-free integration.…”
mentioning
confidence: 99%